Does ethnic voting harm democracy?. Issue 5 (4th July 2018) - Houle, Christian
ABSTRACT: A large literature argues that ethnic voting is detrimental to democracy. Ethnic voting may have at least three effects: (1) it can reduce uncertainty over electoral results; (2) it may increase the winner-take-all character of elections; and (3) it can lead to a process of ethnic outbidding. However, few studies have tested the effect of ethnic voting on democracy using large-N quantitative analysis. Previous tests instead look at whether ethnic fractionalization hinders democracy. Yet, ethnic diversity does not necessarily lead to the politicization of ethnicity, and it is only when ethnicity is activated as a vehicle of political mobilization that it can destabilize democracy. This article tests the effect of ethnic voting in 58 democracies worldwide between 1992 and 2015. On balance, the evidence suggests that democracies with high ethnic voting levels tend to see the quality of their democracy reduce over time relative to those with less ethnic voting. Ethnic and religious fractionalization, however, have little effect.